Implementasi Kebijakan Open Government Data (OGD) dalam Menyongsong Smart City di Kota Surabaya: Studi pada PPID Kota Surabaya - Sultan Wachid , Muhammad; Nathaniela, Amanda; Shalsabila Miracle, Annisaa; Susi Rose Ardian, Anggeli; Hidayatullah, Muhammad; Agus Muljanto, Muhammad (VISA: Journal of Vision and Ideas, 2024)
Rapid urban population growth brings various challenges, such as decreasing quality of public services, reduced residential space, congestion, and increasing crime. Smart City is here as a solution to overcome this challenge and create a city that is safe and comfortable for its residents. Transparency of government data through Open Government Data (OGD) is the key to realizing a Smart City. This research aims to test the implementation of OGD in the City of Surabaya in realizing a Smart City. It is hoped that the research results can provide solutions for relevant agencies and the Indonesian Government in the field of OGD and Smart City. This research applies a descriptive qualitative approach, which adopts an inductive data analysis process to build understanding from specific to general aspects. This approach involves collecting data through in-depth interviews, literature reviews involving previous research published in accredited journals and mass media, as well as utilizing relevant documentation. In this research, it was found that the implementation of smart city in the city of Surabaya can be analyzed through the theory of policy implementation by George C. Edwards III, with aspects of the importance of communication, resources, implementor disposition, and bureaucratic structure. In managing open data, the City of Surabaya has an Information and Documentation Management Officer (PPID) who is responsible for carrying out public information services which include activities for storing, documenting, providing and disseminating information to the public. One of the obstacles to the implementation of open data is that people do not understand the urgency of open government data, so that public intervention and voice of support is also limited. Apart from that, coordination of each unit in each agency that takes part in implementing open government data must also be integrated.